Consumer and asset prices: Some recent evidence - Dieter Gerdesmeier; Hans-Eggert Reimers; Barbara Roffia (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2015)
This paper models the relationship between consumer and asset prices (approximated by house prices, oil prices and the exchange rate) by means of a Markov Switching model (MS model). It can be shown that house prices appear to play a significant role in the determination of consumer prices in a high-inflation and a low-inflation regime, whereas oil prices and the exchange rate only unfold an impact in a high-inflation regime. Taken together, these results can be seen as being of help for the monetary policy decision-making process.
Keywords: D12; D13; E31; 330